Radiographic Analysis of the Sagittal Alignment and Balance of the Spine in Asymptomatic Subjects - Vialle, Raphaël; Levassor, Nicolas; Rillardon, Ludovic; Templier, Alexandre; Skalli, Wafa; Guigui, Pierre (Journal of bone and joint surgery. American volume, 2005)
BackgroundThere is an increasing recognition of the clinical importance of the sagittal plane alignment of the spine. A prospective study of several radiographic parameters of the sagittal profile of the spine was conducted to determine the physiological values of these parameters, to calculate the variations of these parameters according to epidemiological and morphological data, and to study the relationships among all of these parameters.MethodsSagittal radiographs of the head, spine, and pelvis of 300 asymptomatic volunteers, made with the subject standing, were evaluated. The following parameters were measuredlumbar lordosis, thoracic kyphosis, T9 sagittal offset, sacral slope, pelvic incidence, pelvic tilt, intervertebral angulation, and vertebral wedging angle from T9 to S1. The radiographs were digitized, and all measurements were performed with use of a software program. Two different analyses, a descriptive analysis characterizing these parameters and a multivariate analysis, were performed in order to study the relationships among all of them.ResultsThe mean values (and standard deviations) were 60° ± 10° for maximum lumbar lordosis, 41° ± 8.4° for sacral slope, 13° ± 6° for pelvic tilt, 55° ± 10.6° for pelvic incidence, and 10.3° ± 3.1° for T9 sagittal offset. A strong correlation was found between the sacral slope and the pelvic incidence (r = 0.8); between maximum lumbar lordosis and sacral slope (r = 0.86); between pelvic incidence and pelvic tilt (r = 0.66); between maximum lumbar lordosis and pelvic incidence, pelvic tilt, and maximum thoracic kyphosis (r = 0.9); and, finally, between pelvic incidence and T9 sagittal offset, sacral slope, pelvic tilt, maximum lumbar lordosis, and thoracic kyphosis (r = 0.98). The T9 sagittal offset, reflecting the sagittal balance of the spine, was dependent on three separate factorsa linear combination of the pelvic incidence, maximum lumbar lordosis, and sacral slope; the pelvic tilt; and the thoracic kyphosis.Conclusions and Clinical RelevanceThis description of the physiological spinal sagittal balance should serve as a baseline in the evaluation of pathological conditions associated with abnormal angular parameter values. Before a patient with spinal sagittal imbalance is treated, the reciprocal balance between various spinal angular parameters needs to be taken into account. The correlations between angular parameters may also be useful in calculating the corrections to be obtained during treatment.